'An operation under difficulties' 100 years ago. (2nd December 2020) - Ellis, Harold
Abstract : In a change from recalling births, deaths or medical discoveries, this article looks at a paper published in The Lancet 100 years ago. Occupying a little more than a single column, its vivid description of an operation carried out successfully under primitive conditions will be of great interest.